Behavioral Management and Financial Decision-Making: A Literature Review on the Impact of Organizational Culture on Corporate Financial Strategies - Riu, Isma Azis (International Humanity Advance, Business & Sciences, 2024)
This study aims to explore the integration of behavioral management and corporate finance and provide strategies to improve overall corporate performance. The research method used is a review of related literature and research. A qualitative and descriptive approach was used to analyze the relationship between behavioral and financial management in a corporate context. The results show that effective integration between behavioral and financial management can increase employee productivity, improve financial decision-making, and build a strong organizational culture. The necessary strategies include proper recruitment, continuous employee development, effective communication, behavioral financial decision-making, and comprehensive performance evaluation. By implementing this approach, companies can achieve better financial performance and reach their long-term goals.